Exposure to pesticides and risk of amyotrophic lateral sclerosis: a population-based case-control study - Francesca Bonvicini; Norina Marcello; Jessica Mandrioli; Vladimiro Pietrini; Marco Vinceti (Istituto Superiore di Sanità, 2010)
A few epidemiologic studies have suggested an association of agricultural work and pesticides exposure with a severe degenerative disease of the motor neurons, amyotrophic lateral sclerosis (ALS), though conflicting results have also been provided. We investigated through a populationbased case-control study the possible relation between overall occupational exposure to pesticides and ALS risk in the northern Italy municipality of Reggio Emilia. By administering a questionnaire, we investigated occupational history and leisure-time habits of the 41 ALS patients diagnosed in the 1995-2006 period, and of 82 age- and sex-matched randomly sampled population controls. More cases than controls were found to have been exposed to pesticides for at least six months (31.7% vs 13.4%, respectively), in all cases within the occupational environment. In a conditional logistic regression model, we found an excess ALS risk associated with exposure to pesticides, with a relative risk of 3.6 (95% confidence interval 1.2-10.5). Such association persisted after inclusion in the statistical analysis of potential confounders. Despite the limited statistical stability of the risk estimates, these results appear to indicate that occupational exposure to pesticides is a risk factor for ALS, suggesting the need to further investigate this issue.